Investigating the genetic and molecular basis of age-related macular degeneration - Stanton, Chloe May (The University of Edinburgh, 2012)
Age-related macular degeneration (AMD) is the leading cause of blindness worldwide, affecting an estimated 50 million individuals aged over 65 years. Environmental and genetic risk-factors contribute to the development of AMD. An AMD-risk locus on chromosome 10q26 spans two genes, ARMS2 and HTRA1, and controversy exists as to which variants are responsible for increased risk of disease. Recent work suggests that HTRA1 expression levels are significantly increased in carriers of the risk haplotype associated with AMD. However, relatively little is known about the interactions, substrate specificity and roles in disease played by this secreted serine protease. This thesis aims to elucidate the potential role played by HTRA1 in AMD pathogenesis. A combination of tandem affinity purification (TAP) and yeast two-hybrid techniques was used to identify interacting partners of HTRA1. A number of proteins, with diverse roles in the alternative complement pathway, cell signaling, cell-matrix interactions, inflammation, angiogenesis and fibrosis, were identified. These are attractive candidates for further study as such processes are disturbed in AMD, implicating HTRA1 and its binding partners in disease development. One interacting partner, Complement Factor D (CFD), is a key activator in the alternative complement pathway. CFD, a 24 kDa serine protease, is expressed as an inactive zymogen, from which a signal peptide and activation peptide are cleaved before release of the mature, active protein into the circulation. In vitro studies show that CFD interacts with, and can be a substrate for, HTRA1. The interacting domain between the two proteins is localised to a region of 30 amino acids at the N-terminal end of proCFD. The 5 amino acid pro-peptide of CFD appears to be both necessary and sufficient for proteolysis of CFD by HTRA1. Investigation of the functional relevance of the interaction between HTRA1 and CFD shows that proCFD is cleaved by HTRA1, whilst mature CFD is not subjected to proteolysis. HTRA1-mediated cleavage of CFD forms an active protease, leading to activation of factor B in the alternative complement pathway in in vitro assays. Furthermore, a normal complement response is restored to CFD-depleted serum by addition of proCFD activated by HTRA1. Thus, an HTRA1- mediated increase in alternative complement pathway activity may explain a proportion of the AMD-risk attributed to the chr10q26 locus. Genetic and protein-based approaches were used to study the potential role of CFD in AMD pathogenesis, independent of an interaction with HTRA1. An intronic SNP, rs3826945, was significantly associated with increased risk of AMD in two British case-control cohorts, and in a combined meta-analysis with 4 additional cohorts from North America and Europe (p-value = 0.032, Odds Ratio = 1.112 in 4765 cases and 2693 controls). Assessment of copy number variation and sequencing of CFD did not identify any functional variants which may explain the association with disease. However, plasma levels of CFD were measured by ELISA in 751 AMD cases and 474 controls, and were found to be significantly elevated in AMD cases compared to controls (p-value = 0.00025). This further implicates complement activation in AMD pathogenesis, and makes CFD an attractive candidate for therapeutic intervention. An alteration in the level of activated CFD, possibly mediated via an interaction with HTRA1, either at the systemic or local tissue level, may play a role in disease development and progression.
Keywords: Age-related macular degeneration; AMD; HTRA1